2005
DOI: 10.1002/jcp.20346
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage is a potential cause of cone cell death in retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a prevalent cause of blindness caused by a large number of different mutations in many different genes. The mutations result in rod photoreceptor cell death, but it is unknown why cones die. In this study, we tested the hypothesis that cones die from oxidative damage by performing immunohistochemical staining for biomarkers of oxidative damage in a transgenic pig model of RP. The presence of acrolein- and 4-hydroxynonenal-adducts on proteins is a specific indicator that lipid perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
246
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 268 publications
(255 citation statements)
references
References 39 publications
8
246
0
1
Order By: Relevance
“…Using oxygen electrodes, it has been shown that oxygen levels are significantly increased in the outer retina after rods degenerate (5). We have also shown in a transgenic pig model of RP that after disappearance of rods, there is progressive oxidative damage in cones during the period when cones are dying (12). In this study, we showed that in the rd1 mouse model of RP, staining for acrolein, a marker for oxidative damage to lipids, is not detectable in cones at P18 when rod degeneration is just being completed, but by P35, Ϸ2 weeks after the disappearance of most rods and in midst of cone cell death, remaining cones stain for acrolein.…”
Section: Discussionmentioning
confidence: 99%
“…Using oxygen electrodes, it has been shown that oxygen levels are significantly increased in the outer retina after rods degenerate (5). We have also shown in a transgenic pig model of RP that after disappearance of rods, there is progressive oxidative damage in cones during the period when cones are dying (12). In this study, we showed that in the rd1 mouse model of RP, staining for acrolein, a marker for oxidative damage to lipids, is not detectable in cones at P18 when rod degeneration is just being completed, but by P35, Ϸ2 weeks after the disappearance of most rods and in midst of cone cell death, remaining cones stain for acrolein.…”
Section: Discussionmentioning
confidence: 99%
“…This article is a PNAS Direct Submission. 1 To whom correspondence should be addressed. E-mail: xi-qin-ding@ouhsc.edu.…”
Section: Significancementioning
confidence: 99%
“…As mentioned above, oxidative stress has been suggested as one of the causes of cone dysfunction and death in RP (Yu et al, 2004;Shen et al, 2005;Komeima et al, 2006). As the rods die in RP, the flow of oxygen from the choroidal circulation does not abate, and thus each cone is exposed to increasing amounts of oxygen (Yu et al, 2000(Yu et al, , 2004.…”
Section: Treatment With Antioxidantsmentioning
confidence: 99%
“…However, cone death often does not occur until many months after rod death (Carter-Dawson et al, 1978;Milam et al, 1998;Berson, 2008;Lin et al, 2009;Punzo et al, 2009). Another model holds that there is an increase in oxidative damage to cones once the rods have died (Yu et al, 2004;Shen et al, 2005;Komeima et al, 2006). This model also suggests a therapy, that is, delivery of antioxidants or genes encoding antioxidation enzymes.…”
Section: Overview Of Therapeutic Approaches To Rpmentioning
confidence: 99%
See 1 more Smart Citation